A sensitivity analysis to assess the relative importance of improvements in electrocatalysts, light absorbers, and system geometry on the efficiency of solar-fuels generators. Issue 3 (20th January 2015) - Chen, Yikai; Hu, Shu; Xiang, Chengxiang; Lewis, Nathan S.
Abstract : A sensitivity analysis of the relative importance of reductions in the overpotentials of electrocatalysts and of improvements in the material properties of light absorbers. Abstract : A sensitivity analysis has been performed for a variety of generic designs for solar-fuels generators. The analysis has revealed the relative importance of reductions in the overpotentials of electrocatalysts, of improvements in the materials properties of light absorbers, and of optimization in the system geometry for various different types of solar-fuels generators, while considering operation at a range of temperatures as well as under a variety of illumination intensities including up to 10-fold optical concentration.